SOME MORPHOMETRIC STUDIES ON FIVE SPECIES OF CYNOGLOSSUS (FAMILY CYNOGLOSSIDAE, ORDER HETEROSOMATA) FROM THE WEST COAST - Seshappa, G (Indian Journal of Fisheries, 2011)
^Selected morphometricaaii meristic characters Have been analysed in live commonspecies of Cynoglossus at Calicut, namely, C. macrostomus Norman,.'C. dubius Day, Cpuncticeps (^chardson), C. M/nea/Â«s (Lacepede) and C lida (Sleeker). For comparing themorphometrrc ratios Pearson's coeflScient pf variation (P.C.), is used as a measure of thedegree Pf >%riability. The total length/body length ratios >^ere found to be the least variablewhile the ratios connected with the eye and orbit showed the most variable P.C. in allthe species. A comparative table and description are given of the ratios studied of thedifferent characters for the five species chosen. The calculated values of t for the meanratibs in all paired combinations of the five species have been tabulated, and the Probability(P) is found to be significant for most of the comparisons made.